APL : A practical guide for professionals - Simosko, Susan, 1942- (London : Kogan Page, 1991)
Accreditation of Prior Learning (APL) is the process enabling people of all ages, backgrounds and attitudes to gain recognition, credit and qualifications for achievements acquired outside formal education. This book offers guidance for professionals who need to implement and operate an APL system.
Bibliography: p181-183. - Includes index.